Front Cover: Proteomics show antigen presentation processes in human immune cells after AS03‐H5N1 vaccination. Issue 12 (20th June 2017) - Galassie, Allison C.; Goll, Johannes B.; Samir, Parimal; Jensen, Travis L.; Hoek, Kristen L.; Howard, Leigh M.; Allos, Tara M.; Niu, Xinnan; Gordy, Laura E.; Creech, C. Buddy; Hill, Heather; Joyce, Sebastian; et al.
Abstract : DOI:10.1002/pmic.201600453 Adjuvants enhance immune responses elicited by vaccines through mechanisms that are poorly understood. Using a systems biology approach (as represented by the scheme on the cover), temporal protein expression changes were identified and quantified in five primary human immune cell populations: neutrophils, monocytes, natural killer cells, T cells, and B cells after administration of either an AS03‐adjuvanted or unadjuvanted split‐virus H5N1 influenza vaccine. For more details, see the article by Allison C. Galassie et al., article number 1600453. [Cover design by Johannes B. Goll and Andrew J. Link]